Inflation in Turkey - Bahtiyar Berk (GoAcademica Research & Publishing, 2023)
Inflation is an economic phenomenon that has been a primary concern in many countries, including Turkey. This journal article aims to depict the evolution of inflation in Turkey over recent years, along with the factors influencing it. The authors will present empirical data and theoretical analysis of inflation in Turkey, as well as relevant policy implicationsTurkey has witnessed a complex inflationary landscape characterized by fluctuations in the past few decades. This article provides an overview of Turkey's inflationary history, starting from the aftermath of the 2001 financial crisis to the more recent challenges posed by global economic dynamics, such as rising oil prices, exchange rate volatility, and domestic demand pressures. It also delves into the pivotal role of monetary and fiscal policies in the battle against inflation.